Egg Quality of Tegal Ducks in Intensive Keeping Feed with Different Levels of Methionine and Lancang (Atlanta sp.) - Roesdiyanto, Roesdiyanto (ANIMAL PRODUCTION, 2002)
The purpose of this research is to study the effect of combination levels of methionine-lancang (Atlanta sp.) in diet on egg quality of Tegal ducks. Eighty-one Tegal ducks early production period were used in this research. The treatments were arranged in a factorial (3x3). The first factor was level of synthetic methionine supplement (M) comprised of  m1: 0,00%, m2: 0,05%, and m3: 0,10%. The second factor was level of lancang (L), i.e. l1: 0,0%, l2; 2,0%, and l3: 4,0%. The variables observed were eggshell-thickness, haugh unit, and egg index. The result showed that the average eggshell-thickness was 0,335 ± 0,002 mm, range between 0,317 to 0,337 mm. The average of haugh unit was 92,054 ± 2,906 range between 85,767 to 99,095, and average of egg index was 76,58 ± 2,91, range between 73,79-81,37%. The interaction of methionine-lancang did not have significant effect on eggshell thickness, haugh unit, and egg index during the first two months egg production. Level of methionine significantly different (P<0,05) the haugh unit, but did not affect eggshell thickness and egg index. Level of  lancang has affect (P<0,05) eggshell thickness significant, but did not significant affect the haugh unit, and egg index. It can be concluded that increasing of synthetic methionine in the diet until 0,10% can improve haugh unit, and increase of lancang until 4,0% can improve eggshell thickness. (Animal Production 4(2): 77-82 (2002) Key words : Egg Quality, Tegal Duck, Intensive, Methionine, Lancang